Assessment and grouping of occupational magnetic field exposure in five electric utility companies - Kromhout, Hans; Loomis, D. P.; Mihlan, G. J.; Peipins, L. A.; Kleckner, R. C.; Iriye, R.; Savitz, D. A. (Scandinavian Journal of Work, Environment & Health, 1995)
' ' OBJECTIVES ': 'Occupational exposure to 60-Hz magnetic fields was surveyed among randomly selected workers in five electric power companies.' ' METHODS ': 'The study facilitated the examination of exposure variability and provided the base for a job-exposure matrix linking health outcomes and occupational magnetic field exposures.' ' RESULTS ': 'Average exposures ranged from 0.11 to 1.50 µT. The differences among the five companies were small, the more urban companies showing somewhat higher averages. The day-to-day component of variance exceeded the within- and between-group components of variance. The final job-exposure matrix consisted of five groups with average exposure levels of 0.12, 0.21, 0.39, 0.62, and 1.27 µT. Given the variance in exposure, even this optimal grouping considerably overlapped. Conclusions The job-exposure matrix used in this study efficiently incorporated the differences in exposure within occupational categories between companies and provided an objective and statistically based method for estimating cumulative magnetic field exposure.
Keywords: exposure assessment; exposure level; magnetic field; misclassification; occupational exposure; precision; resolution